Pileflebitis: reporte de caso y revisión de literatura - Lizeth Mirtha Flores Anaya (2015)
We present the case of a 50-year-old man who comes to the emergency department of Dos de Mayo Hospital, Lima, Peru, with fever, abdominal pain, diarrhea and jaundice. An intestinal infection arises as initial diagnosis. He is referred to the area of Internal Medicine where various laboratory tests and imaging studies were conducted, including an abdominal computerized tomography scan. The scan confirmed the diagnosis of pylephlebitis; treatment with antibiotics and anticoagulant therapy was immediately established. Response and evolution were favorable.